Avaliação de vulnerabilidade das águas subterrâneas à contaminação na bacia do rio Urubu, Tocantins - Silva, Fábio da Costa (Universidade Federal do Tocantins, 2021)
The analysis of the vulnerability of groundwater to the contamination of a basin comprises the study of the intrinsic physical characteristics that drive the behavior of aquifers under the risks of contamination which comes along with the variety of land uses and land covers that exists. The main objective of this work is to evaluate the vulnerability of groundwater to contamination in the Urubu river basin, Tocantins State. The groundwater vulnerability index VIX was used to perform the studies, as well as the characterization of land uses and land cover in the basin, and two other complementary indices: NDWI index (Normalized Water Difference Index) to identify areas with the highest water content on the land surface and the Soil Physical Quality S index to diagnose degraded areas. The dissertation presents the results of the article entitled “Analysis of groundwater vulnerability to contamination.” In this study, a total of 15 areas of the Urubu River basin were selected so that they represented the different categories of land use and land cover that were previously identified. The study made it possible to construct a groundwater vulnerability map by applying the VIX index. In addition, this work aimed to identify areas which are likely to accumulate water by using the NDWI index values. The results showed that the shallow depth of the groundwater influenced on the high values of the VIX index of the areas located to the west side of the basin, indicating that the groundwater in that region is more susceptible to contamination. It was also observed that the positive NDWI values found in the western basin corroborate the condition of groundwater vulnerability due to the higher water content in the soil which increases the groundwater exposure to the human activities. The results section of this dissertation also presents the article “Characterization of land use and land cover and physical quality of soils in the Urubu River basin, Tocantins”. The study’s objective was characterizing the land use and land cover in the Urubu River basin. The study also analyzed the physical quality of 15 soil samples that were extracted from different existing land uses and land cover. It was observed that the Urubu River basin is still covered by 58% of its native vegetation (savannas and forest formations) and that agricultural activity occupies 30% of the lands in the study area. Despite the nature of the land use or land cover of the basin, all soil samples were diagnosed as degraded soils due to the poor physical quality indicated by the S index. The study showed the need for sustainable management practices to ensure the physical quality of soils, and consequently surface and groundwater of the Urubu river basin. Overall, the results presented in this dissertation showed that there are areas in the western portion of the Urubu river basin where, considering the predominant land uses and the values of VIX and NDWI, there is a context of greater groundwater vulnerability to contamination. Thus, the present study is positioned as a relevant tool in the management of groundwater resources of the Urubu river basin.